Theoretical Determination of Binding Energies of Small Molecules on Interstellar Ice Surfaces - Duflot, Denis; Toubin, Céline; Monnerville, Maurice (Frontiers in Astronomy and Space Sciences, 2021)
The adsorption of a series of atoms and small molecules and radicals (H, C, N, O, NH, OH, H2O, CH3, NH3) on hexagonal crystalline and amorphous ice clusters were obtained via classical molecular dynamics and electronic structure methods. The geometry and adsorption energy were calculated using a QMHigh:QMLow hybrid method on model clusters. Several combination of basis sets, density functionals and semi-empirical methods were compared and tested against previous works. More accurate adsorption energies were also refined via single point Coupled Cluster calculations. Most species, except carbon atom, physisorb on the surface, leading to rather small binding energies. The carbon atom forms a COH2 molecule and in some cases leads to the formation of a COH-H3O+ complex. Amorphous ices are characterized by slightly stronger adsorption energies than the crystalline phase. A major result of this work is to also access the dispersion of the binding energies since a variety of adsorption sites is explored. The interaction energies thus obtained may serve to feed or refine astrochemical model. The present methodology could be easily extended to other types of surfaces and larger adsorbates.